Pro .NET 2.0 Extreme Programming - Pearman, Greg (Apress, 2012)
Many books cover the theory of Extreme Programming (XP). This is not one of them. If you are picking up this book hoping to learn about the philosophy of XP, you will be disappointed. This book concentrates on the practical, not the theoretical. We hope to leave you with the knowledge of how to implement XP in a practical manner. But before we do this, we need to give you a clear, no-nonsense definition of XP. To put XP in context, we’ll begin by looking briefly at the waterfall and Agile methods of software development. Each methodology has many books dedicated to it, of course. Here, we will give you just enough information to understand how and why XP came to exist. Then we’ll answer the question “What is XP?” We’ll look at all of the specific key values, principles, and practices of XP. You’ll know what XP is after you have read this section! Next, we’ll offer you a comparison between XP and some other current Agile methods. Finally, we’ll address when it’s best to use XP.0